(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes the problems of import substitution for the most import-dependent branches of the economy of the Russian Federation: mechanical engineering, chemical industry, metallurgy and agro-food sector, the development and functioning of which was complicated by imposed sanctions on the part of the EU, USA and other countries as a result of aggression of the Russian Federation against Ukraine and the occupation of the Autonomous Republic Crimea. Relevance of the research topic due to the economic consequences of the systemic exposure of sanctions of the EU, the United States and other Western countries, which have arisen as a result of Russian aggression against Ukraine and occupation of the Autonomous Republic of Crimea. The aim of the article is to highlight the issues of import to the most import-dependent sectors of the Russian economy. The article analyzes the anti-crisis measures of the Russian government. Based on the method of comparative analysis the effectiveness of the results of the priority actions for the sustainable economic development and social stability of the Russian Federation is examined. Three types of import dependence and hence import substitution in terms of mobilization of the economy of the Russian Federation are identified and analyzed. It is proved that the Russian Federation will not be able to restrict the creation of a favorable investment climate for the economy in general and will need mechanisms of «manual» control for import substitution projects in crisis conditions. It is proved that under the conditions of the mobilization of the economy of the Russian Federation should significantly increase the role of agri-food industries, and the limitations of investments and other productive resources will force to return to the issue of defense sufficiency.